LncRNA SNHG6/miR-125b-5p/BMPR1B Axis: A New Therapeutic Target for Triple-Negative Breast Cancer - Lv, Yufei; Lv, Xiaohong; Yang, Huike; Qi, Xiuying; Wang, Xiangchen; Li, Chao; Shang, Xiaochen; Guo, Hongmin; Zhang, Jianguo; Zhang, Yafang (Frontiers in Oncology, 2021)
Background: Triple-negative breast cancer (TNBC) is a significant cause of patient morbidity. The exactly pathobiological features of this condition has yet to be completely elucidated. Methods: Breast cancer data obtained from The Cancer Genome Atlas (TCGA) database were evaluated for lncRNA SNHG6 expression. Normal human breast epithelial cell line (MCF-10A) and other breast cancer cell lines (BT-549, MDA-MB-231, Hs 578t, ZR-75-30, SK-BR-3, MCF-7) were also assessed for lncRNA SNHG6 expressions. Cellular proliferative ability was evaluated with colony formation and CCK-8 assays. The ability of cells to migrate was scrutinized with the wound healing and Boyden chamber cell migration assays. qRT-PCR enabled for detection of lncRNA SNHG6, miR-125b-5p and BMPR1B mRNA expressions. Protein BMPR1B expressions were further assessed using Western Blotting. Direct binding sites between transcripts were determined using luciferase reporter assays. We also constructed a xenograft mouse model to further dissect the vivo implications of lncRNA SNHG6. Ki-67 expressions were detected using immunohistochemistry staining. Results: Breast cancer cell lines demonstrated higher lncRNA SNHG6 expressions, particularly TNBC cell lines, in contrast to normal breast epithelial cell lines. This finding coincided with those noted on analysis of TCGA breast cancer data. lncRNA SNHG6 knockdown inhibited TNBC cell proliferation, migration, and invasion. Furthermore, suppressed lncRNA SNHG6 expressions resulted in lower tumor weights and volumes in a xenograft mouse model, as evidenced by Ki-67 expression profiles in tumor tissues. miR-125b-5p and lncRNA SNHG6/BMPR1B both possessed direct binding sites for each other which was validated utilizing a dual-luciferase reporter assay. Decreasing lncRNA SNHG6 expression in TNBC cells upregulated miR-125b-5p expression. Another side, inhibiting miR-125b-5p upregulated BMPR1B expression in these cells. Moreover, knocking down lncRNA SNHG6 downregulated BMPR1B expression in TNBC cells, a finding that was rescued in cells which were also exposed to miR-125b-5p inhibitor. Downregulating miR-125b-5p mitigated the inhibitive effect of suppressing lncRNA SNHG6 on TNBC cell proliferation, migration, and invasion. Conclusion: Downregulation of lncRNA SNHG6 could inhibit TNBC cell proliferative, migratory and invasive capabilities, likely through modulation of the miR-125b-5p/BMPR1B axis. This axis may be targeted in formulating new therapies for TNBC.